Assessment of local and systemic signature of eosinophilic esophagitis (EoE) in children through multi-omics approaches - Adel-Patient, Karine; Campeotto, Florence; Grauso, Marta; Guillon, Blanche; Moroldo, Marco; Venot, Eric; Dietrich, Céline; Machavoine, François; Castelli, Florence A.; Fenaille, François; Molina, Thierry Jo; Barbet, Patrick; et al. (Frontiers in Immunology, 2023)
Eosinophilic oesophagitis (EoE) is a chronic food allergic disorder limited to oesophageal mucosa whose pathogenesis is only partially understood. Its diagnosis and follow-up need repeated endoscopies due to absence of non-invasive biomarkers. We aimed to deeply describe immunological and molecular components of EoE in well-phenotyped children using complementary approaches, i.e. local transcriptomics, comprehensive analysis of local and systemic immune constituents, and plasma metabolomics. Blood and oesophageal biopsies were collected from French children with EoE (n=17) and from control subjects (n=15). Global transcriptomics analysis was performed on mRNA extracted from biopsies using microarrays. Comprehensive analysis of immune components was performed on cellular and soluble extracts obtained from both biopsies and blood using flow cytometry. Non-targeted plasma metabolomics was performed using liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS). Uni/multivariate supervised and non-supervised statistical analyses were then conducted to identify components associated with EoE within local and/or systemic transcriptomics, immunologic and metabolomics datasets. As a proof of concept, we conducted multi-omics data integration to identify a signature of EoE in plasma. We evidenced French children with EoE shared the same transcriptomic signature as US patients, with a very high correlation of differentially expressed (DE) genes and of their fold changes. Network visualization of DE genes highlighted the major dysregulation of innate and adaptive immune processes, but also of pathways involved in epithelial cells and barrier functions, and in perception of chemical stimuli. Immune analysis of biopsies highlighted EoE-associated dysregulation of both type (T) 1, T2 and T3 innate and adaptive immunity, in a highly inflammatory milieu. Although an immune signature of EoE was found in blood, untargeted metabolomics more efficiently discriminated children with EoE from control subjects, with notably dysregulation of vitamin B6 and various amino acids metabolisms. Multi-blocks integration suggested that an EoE plasma signature may be identified by combining metabolomics and cytokines datasets. Our study strengthens the evidence that EoE results from alterations of the oesophageal epithelium associated with altered immune responses far beyond a simplistic T2 dysregulation. As a proof of concept, combining metabolomics and cytokines data may provide a set of potential plasma biomarkers for EoE diagnosis.